THE INFLUENCE OF GOOD CORPORATE GOVERNANCE ON INTERNET FINANCIAL REPORTING (Study on Financial Sector Banking Sub-Sector Listed in the Indonesia Stock Exchange (IDX) from 2013 to 2020 - Nurlaily, Ferina; -, Nur Aini Hana Pratiwi (Profit: Jurnal Adminsitrasi Bisnis, 2022)
This study determines the effect of Good Corporate Governance on Internet Financial Reporting (IFR) in banking companies in Indonesia. Sample research consists of 5 banks listed on the IDX during 2013-2020. This study uses the IFR as the dependent variable, and the independent variable consists of managerial ownership, independent commissioner, the frequency of the audit committee meeting, and the competency of the audit committee. An Explanatory Research is implemented in this study with multiple linear regression analysis. Research finding indicates that partially the independent commissioner and the competence of the audit committee deliver significant effect on the disclosure of IFR, while managerial ownership and the frequency of the audit committee meeting give an otherwise result. Keywords: Banking Companies, Competency of Audit Committee, Frequency of The Audit Committee Meeting, Independent Commissioner Managerial Ownership, Internet Financial Reporting.